Implementasi Kombinasi Model Pembelajaran Pjbl, Pakem Dan Collaborative Learning Dalam Upaya Meningkatkan Aktivitas Dan Hasil Belajar Muatan Ipas Pada Siswa Kelas 4 Sdn Alalak Utara 3 Kota Banjarmasin - Muhammad Saukani; Mahmuddin . (CV. ITTC INDONESIA, 2024)
One of the problems faced by students in this study is their lack of ability to think critically. They also face difficulties in remembering and understanding the subject matter, do not have a strong desire to participate in learning, and are not active during the learning process. Combining the PjBL, PAKEM, and Collaborative learning models is an effort to overcome this problem. The purpose of this study was to analyze how teacher activities, student activities, and student learning outcomes can be improved in quality. Classroom action research was conducted in three meetings with a qualitative approach. Grade 4 students of SDN Alalak Utara 3, totaling 29 students, consisting of 13 male students and 16 female students, were involved in the study during the second semester of the 2023/2024 academic year. Data were collected by observing teacher and student activities, as well as student learning outcomes. Classical learning completion indicators and percentage scales were used to calculate data analysis. The results showed that project-based learning models, PAKEM, and collaborative learning can be used to improve student learning outcomes. Teachers showed increased activity at the third meeting by obtaining a score of 33 in the